2004
DOI: 10.1063/1.1830083
|View full text |Cite
|
Sign up to set email alerts
|

Growth and luminescence properties of micro- and nanoneedles in sintered CdSe

Abstract: Sintering CdSe powder under argon flow at temperatures in the range 800–900 °C produces the formation of needles on the sample surface. Bundles of parallel needles of a diameter of about 50 nm give rise to a domain-like appearance in the sample. In addition, rods and needles with a wide range of dimensions up to several microns appear distributed in the surface. The influence of ball milling of the starting powder on the formation of the needles is investigated. Cathodoluminescence in the scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…This contrast could be associated to an increase of defect concentration around twins which could easily appear in the intersection of the branch with the main steam [24]. Similar behaviour has been observed in other materials as CdSe [14]. In many cases, instead of the pencil like shape shown in Figs.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…This contrast could be associated to an increase of defect concentration around twins which could easily appear in the intersection of the branch with the main steam [24]. Similar behaviour has been observed in other materials as CdSe [14]. In many cases, instead of the pencil like shape shown in Figs.…”
Section: Resultssupporting
confidence: 57%
“…2c). The CL distribution shows that the core of the crystals is darker, an opposite behaviour to that found from hollow structures of several semiconductors [14,25] in which the inner part is much brighter. Closest to the gas inlet, nanocombs, and nanoneedles are obtained.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is a useful technique for the characterization of the optical properties of nanostructure because of its high spatial resolution and structural information obtained by using secondary electron (SE) imaging. [9][10][11][12][13][14][15] Field-emission (FE) is based on the physical phenomenon of quantum tunneling, during which electrons are injected from a material surface into a vacuum under the influence of an applied electric field. Since the discovery of carbon nanotubes (CNTs), much attention has been paid to the prospects of 1D micro/nanostructures as field emitters because of their low work functions, high aspect ratios, high mechanical stabilities, high conductivities, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Previous cathodoluminescence measurements of single CdSe needles, 5 ZnSe nanorods 6 and ZnO nanowires 7 have indicated that morphology can influence their emission. Here, direct optical imaging of a number of single VLS-prepared CdS nanowires reveal two distinct types of emission: a spectral band emitting at energies associated with free and bound exciton emission from CdS, and spatially localized states at lower energy which we relate to morphological irregularities of the nanowires.…”
mentioning
confidence: 99%